Exploring the Interplay Between Adversity, Neurocognition, Social Cognition, and Functional Outcome in People With Psychosis: A Narrative Review - Rodriguez, Victoria; Aas, Monica; Vorontsova, Natasha; Trotta, Giulia; Gadelrab, Romayne; Rooprai, Navneet Kaur; Alameda, Luis (Frontiers in Psychiatry, 2021)
History of adversity is associated with subsequent psychosis, and with a spectrum of cognitive alterations in individuals with psychosis. These cognitive features goes from neurocognitive aspects as working memory and attention, to complex social cognitive processes as theory of mind and emotional perception. Difficulties in these domains impact patients’ social and occupational functioning, which has been shown to be more impaired in those previously exposed to childhood trauma. However, the interplay between adversity, neurocognition and functioning is yet poorly understood. This narrative review aims to explore the evidence on whether deficits in neurocognitive and social cognitive domains may act as possible putative mechanism linking adversity with functioning in people with psychosis. We show available evidence supporting the link between adversity and poorer functioning in psychosis, especially in chronic stages; and replicated evidence suggesting associations of social cognition and, to a lesser extend, neurocognition with impairment in functioning in patients; although there is still an important gap in the literature testing particularly deficits in social cognition as mediator of the link between adversity and functional decline in psychosis. Targeting interventions focusing on neurocognition and social cognition in individuals with adversity and psychosis seems important, given the severe deterioration of these patients in these domains, although more research is needed to test whether such treatments can specifically improve functioning in individuals with psychosis and adversity. Literature aiming to understand the determinants of functional outcome should consider the pervasive impact of childhood adversity, and its related effects on cognition.